A Cephalometric Evaluation and Comparison of Skeletal, Dentoalveolar, and Soft Tissue Changes Brought about by the Forsus Fatigue Resistant Device and PowerScope Fixed Functional Appliance. Issue 3 (July 2022) - Kaur, Gabbie Jasmine; Gandhi, Geetanjali; Khanna, Mannu; Loomba, Anju; Sharma, Atul
Background: Though studies have been conducted on the PowerScope, not many researches are available in the literature which compare its effects with other fixed functional appliances. Therefore, the aim of our study was cephalometric evaluation and comparison of the skeletal, dentoalveolar, and soft tissue changes brought about by the Forsus Fatigue Resistant Device and PowerScope appliance. Materials and Methods: Pre and Posttreatment cephalometric records of 20 patients with Class II Division 1 malocclusion treated with fixed functional appliances (Forsus Fatigue Resistant Device and PowerScope) were compared. Values of various cephalometric parameters were used to evaluate the skeletal, dental, and soft tissue changes. Wilcoxon signed-rank test (intragroup comparison) and Mann–Whitney U test (intergroup) were used to see significant differences in the parameters ( P ≤ .05). Results: Both the appliances were successful in correcting the Class II discrepancy. Skeletal changes were seen significantly in both the groups, though they were more in the Forsus patients. Dentoalveolar changes were predominantly seen in PowerScope patients. Also, an improvement in soft tissue profile was seen in both the groups. Conclusion: From our study, we concluded that the PowerScope and the Forsus Fatigue Resistant Device are equally good options for the correction of skeletal Class II malocclusion due to a retrognathic mandible, as they achieve changes in all the three aspects: skeletal, dentoalveolar and soft tissue.